2017
DOI: 10.1038/aps.2017.89
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 suppresses cell proliferation in human breast cancer by directly targeting FOXA1

Abstract: Dysregulation of microRNAs (miRNAs) has been implicated in cancer. Recently, miR-132 has been reported to be downregulated in the tissues of patients with breast cancer. In this study, we investigated the functional role of miR-132 and its direct target FOXA1 in breast cancer cells. In 30 human breast cancer tissues, FOXA1 was significantly overexpressed and negatively correlated with miR-132 expression. A bioinformatics analysis suggested that FOXA1 was a potential target of miR-132. Furthermore, dual lucifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In the present study, prediction software analysis showed that multiple miRNAs may regulate LAPTM4B, and common predictive results were evident in at least three databases for hsa-miR-132-3p, hsa-miR-139-5p, hsa-miR-582-5p and hsa-miR-625-5p. [27][28][29][30][31] Moreover, luciferase Multiple studies have proven that differentially expressed miRNAs could widely modulate the proliferation, invasion and metastasis of breast cancer. miR-99a inhibited the activation process of the phosphorylation of mTOR and its downstream molecules 4E-BP1 and S6K1, eventually suppressing the proliferation of MCF-7 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, prediction software analysis showed that multiple miRNAs may regulate LAPTM4B, and common predictive results were evident in at least three databases for hsa-miR-132-3p, hsa-miR-139-5p, hsa-miR-582-5p and hsa-miR-625-5p. [27][28][29][30][31] Moreover, luciferase Multiple studies have proven that differentially expressed miRNAs could widely modulate the proliferation, invasion and metastasis of breast cancer. miR-99a inhibited the activation process of the phosphorylation of mTOR and its downstream molecules 4E-BP1 and S6K1, eventually suppressing the proliferation of MCF-7 and MDA-MB-231.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-132, which was shown to target FOXA1, was reduced in peripheral blood of both HF patients and HF-induced rats. In vitro studies demonstrated that miR-132 overexpression in cells treated with H 2 O 2 reduced apoptosis and oxidative stress through increasing SOD levels and reducing MDA levels [58]. In addition, miR-132 overexpression reduced Transforming growth factor-β1 (TGF-β1) and Smad3, two important pro-fibrotic factors, suggesting an overall cardioprotective role for miR-132, which was abolished by its downregulation in HF [59].…”
Section: Mirna Induction Of Oxidative Stress In Hfmentioning
confidence: 99%
“…FOXA1 is expressed in various organs, including breast, liver, pancreas, and prostate, and can influence the expression of a large number of genes associated with metabolic processes, regulation of signaling, and the cell cycle [29,30]. It has been reported that Foxa1 was a direct target of miR-132 in breast cancer, thyroid cancer, and nasopharyngeal carcinoma [31][32][33]. In consistent with the above results, our research further proved that FOXA1 was a direct target of miR-132 in KGN cells proliferation.…”
Section: Discussionmentioning
confidence: 99%